Politics of the Russian language beyond Russia - Noack, Christian (Russian language and society., 2021)
Russian policy documents increasingly emphasise the importance of "miagakaia sila" (soft power) for securing Russia's foreign policy interests. Looking at the politics of Russian in a range of countries including the Ukraine, Belarus, Kazakhstan, Moldova, Ireland and Germany, this book examines Russian language promotion and its reception in different countries and across different contexts.